Anterior chamber depth and its associations with ocular and general parameters in adults - Jonas, Jost B. (Clinical & experimental ophthalmology, 2012)
Background: To investigate the normative data of anterior chamber depth and its associations in adults in rural Central India. Design: Population-based study. Participants: The Central India Eye and Medical Study included 4711 subjects aged 30+ years (response rate 80.1%). Methods: The subjects underwent an ophthalmological examination including measurement of the anterior chamber depth by sonography. Main Outcome Measure: Anterior chamber depth. Results: Mean anterior chamber depth was 3.22 ± 0.34 mm. In multivariate analysis, a shallow chamber depth was significantly associated with higher age (P < 0.001), female gender (P < 0.001), shorter body stature (P = 0.003), hyperopic refractive error (P < 0.001), higher lens thickness (P < 0.001) and shorter axial length (P < 0.001). Conclusions: In the rural Central Indian population, a shallow anterior chamber was associated with higher age, female gender, short body stature, hyperopia, thick lens and shorter axial length. Compared with population-based data from East Asia (China), the anterior chamber was markedly deeper in India. The data may be helpful to explain anatomic relationships of the anterior segment of the eye, to elucidate risk factors of angle-closure glaucoma and to explain ethnic differences in the prevalence of angle-closure glaucoma.